Organizational Dress as a Symbol of Multilayered Social Identities - Pratt, Michael G.; Rafaeli, Anat (Academy of Management Journal, 1997)
Qualitative data collected in a rehabilitation unit of a large hospital reveal how organization members used dress to represent and negotiate a web of issues inherent to the hybrid identities of the unit and the nursing profession. As different issues were considered, dress took on various and often contradictory meanings. Thus, a seemingly simple symbol such as organizational dress is shown here to reveal the complex notion of social identity, which is argued to comprise multiple layers of meaning. We discuss the implications of this thesis for theory and research on organizational identity, organizational symbolism, organizational dress, and ambivalence.